Incorporación de yogurt de yuca en la alimentación de codorniz hembras en la etapa de crecimiento - Manobanda Rumiguano, Maycol David (2023)
Establishing quail breeding is a practice that requires a small space for each bird housed. Regarding feeding, alternative foods can be introduced that meet the nutritional requirements of the birds. This aspect is particularly relevant compared to other poultry farming practices. The objective of this research work was to analyze the incorporation of cassava yogurt in the diet of female quails in the growth stage. The main materials used in this project were: quail, cassava, milk, yogurt, feed and water. The ANOVA method was used with a classification factor, also called Completely Randomized Design (DCA), is the simplest of the experimental designs to compare different populations and evaluate their variability, which consisted of 3 repetitions and 4 treatments in the T1 for each liter of water 15 ml of cassava yogurt, in T2 they were given 20 ml of cassava yogurt for each liter of water and in T3 they were given 25 ml of cassava yogurt for each liter of water. Run-of-the-mill T0 treatment will not be relevant. The treatments in which cassava yogurt was established obtained responses in both growth and food efficiency in the breeding of female quail, on the productive parameters of cassava yogurt in female quail, positive impacts were observed on growth and development. Treatment 1 stood out by presenting a greater weight in week 3, reaching 185.17 g. In terms of live weight gain in the same week, treatment 1 achieved 175.03 g. Regarding food consumption, treatment 1 recorded a consumption of 1294.90 g. Based on mortality, cassava yogurt in the quail diet has proven to be effective in reducing the mortality rate, reaching 0% during the study period. While the incorporation of cassava yogurt in the quail diet during the period from start to lay (45 days) reveals that treatment 2 stood out with the best cost benefit, reaching $1.70. This means that for every $1 invested during the study, $0.70 cents were recovered.